Impact of Financial Decisions on Corporate Value in Indonesia: Dampak Keputusan Keuangan terhadap Nilai Perusahaan di Indonesia - Noviana, Mahmudah Ayu; Nurasik (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of investment decisions, funding decisions, company size, and financial performance on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2019. Utilizing quantitative methods and secondary data from annual financial reports of 26 companies, the research employs statistical analysis techniques to a purposive sample of 10 firms. Results indicate that while investment and funding decisions did not significantly affect firm value, company size demonstrated a significant influence, whereas financial performance did not exhibit a significant effect. These findings offer valuable insights for managers and investors aiming to enhance company performance and value in the Indonesian market. Highlight: Investment and funding: Crucial for company's financial health and prospects. Company size: Influences firm value, indicating scalability's importance in perception. Implications: Insights for optimizing performance and value in Indonesian market. Keywoard: Investment decisions, Funding decisions, Company size, Financial performance, Firm value